“Life must go on” Afizfaiz - UMP, PNC (2018)
Kuala Lumpur, 1 September – It has been a bittersweet experience for Ahmad Afizfaiz Roslan, 19, but life must go on. Having to come for registration day without the loved one, is never an easy things to do.